Further development of silk sericin as a biomaterial: comparative investigation of the procedures for its isolation from Bombyx mori silk cocoons - Chirila, Traian V. (Prog Biomater, 2016)
There is significant research dedicated to fibroin and sericin, the two major proteinaceous components of the silk threads produced by the domesticated silkworm, Bombyx mori. While fibroin is accepted as an established biomaterial, sericin (BMSS) has been largely neglected in this respect on the account of a hypothetical allergenic activity. Research over the past decade, including our previous study (Prog Biomater 2:14, 2013), demonstrated the biocompatibility of sericin and feasibility of its use as a biomaterial. However, the current procedures for isolating BMSS from the raw silk cocoons can only provide degraded proteins, where the size and distribution of their molecular masses are significantly altered. Based on the plausible assumption that such effects can have a negative impact on the properties of sericin as a biomaterial, in this study we investigated comparatively four different extraction procedures in order to find the method that would cause the least hydrothermal degradation of BMSS. The products resulting from commonly used procedures (extraction in boiling water, alkaline extraction, and extraction in autoclave) were compared to those resulting from aqueous extraction in mild conditions as described a long time ago by Anderlini. The molecular mass distribution in BMSS resulting from each procedure was examined by electrophoretic analysis performed on sodium dodecyl sulphate-polyacrylamide gel (SDS-PAGE), while the conformational changes pertaining to secondary structure of BMSS were evaluated by Fourier transform infrared-attenuated total reflectance (FTIR-ATR) spectrometry. The electrophoretograms indicated that the aqueous extraction in mild conditions conducted at 50 °C for durations up to 4 weeks, with/without stirring, afforded the least degraded BMSS. The infrared spectrometric analysis showed that BMSS resulting from the mild extraction method contained predominantly β-sheet conformations, while the more degradative methods (alkaline, autoclave) led to BMSS where the random-coil conformations were preferential. The long-duration aqueous extraction at 50 °C (but not at 60 °C) appeared as a valid option for obtaining BMSS products where the hydrothermally induced fragmentation of the polypeptidic components is minimized.